2021
DOI: 10.1007/s10597-021-00835-4
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Mental Health Through Bhutanese Refugee Lens: Findings from a Mixed Methods Study

Abstract: Despite the rapidly growing need to understand mental health challenges faced by refugee subpopulations, there is a dearth of literature exploring mental health conceptualization through the unique refugee lens. Guided by historical trauma theory, we gathered data using a two-phase explanatory sequential mixed-methods study (quantitative: n = 40; qualitative: n = 6) in a Midwestern U.S. region to understand mental health conceptualization from the Bhutanese refugee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Studies of the perceptions of mental illness in the Somali, Syrian, and Bhutanese refugees revealed that these groups share a strong focus on religion (Al Laham et al, 2020;Bettmann et al, 2015;Maleku et al, 2021). The study on Syrian refugees in the rural area of Wadi Khaled in Lebanon described that, in this community, religious healers are culturally acceptable and less stigmatizing to go to for mental health problems than mental health professionals (Al Laham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the perceptions of mental illness in the Somali, Syrian, and Bhutanese refugees revealed that these groups share a strong focus on religion (Al Laham et al, 2020;Bettmann et al, 2015;Maleku et al, 2021). The study on Syrian refugees in the rural area of Wadi Khaled in Lebanon described that, in this community, religious healers are culturally acceptable and less stigmatizing to go to for mental health problems than mental health professionals (Al Laham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of family members would be especially beneficial for certain refugees from Myanmar, because the pregnant refugees' most commonly used treatment was emotional and social support from family and close friends (Fellmeth et al, 2015). The involvement of family would also benefit Bhutanese refugees, who discussed seeking social support in order to cope (Maleku et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our mixed methods approach to data collection was reviewed and determined exempt by the Office of Responsible Research Practices (ORRP-OSU Study ID 2021E9088) and is a part of the transformative paradigm we developed to foster coproduction and engagement between Bhutanese community members and academicians (see Figure 1 ). Using a three-phased explanatory sequential mixed methods research design [ 23 ], we integrated (1) geographic information systems to inform (2) quantitative and (3) qualitative data collection. While this paper is based upon quantitative data and the open-ended responses to our survey, our larger study combines mapping, quantitative data, surveys, and ethnography to identify physical, social and health inequalities around the digital divide.…”
Section: Methodsmentioning
confidence: 99%
“…Refugees migrating to another country often have prior experiences of persecution, violence, loss of social networks and physical and psychological trauma (Fazel et al, 2005; Jankovic et al, 2013; Porter and Haslam, 2005). As refugees resettle in host countries, they face postmigration stressors related to housing, employment, access to health and human services, language and inclusion in new spaces, among other concerns (Beiser and Hou, 2016; Maleku et al, 2022; Um et al, 2015).…”
Section: Introductionmentioning
confidence: 99%